English language teachers’ perceptions of world Englishes and English as a lingua franca - Özdenur Ardıç Kıyak (Literacy Trek, 2021)
English language has already become a world language while the world is changing and globalizing. It has been universally accepted in the academic field that English is now used as a lingua franca (ELF) in intercultural communication, and the lingua franca role of English has started to affect teacher education. Although there have been many of studies about ELF and World Englishes (WE), the perceptions of English language teachers require more investigation to describe the position of English in English Language Teaching (ELT) context. Therefore, this exploratory study aimed to investigate the perceptions of English language instructors who work at different state and foundation universities and English language teachers who work at different institutions at primary, secondary, high school and university level during 2019- 2020 spring semester in Turkey. For this purpose, their perceptions of ELF and ELF-related issues concerning cultural aspects, Standard English and World Englishes, as well as the native and non-native dichotomy were explored through a questionnaire. The results were interpreted to present several implications for language learners, teachers/instructors, material developers and curriculum designers.